Explaining Qur’anic Verse Selection in the State Funeral of Ayatollah Ali Khamenei through Revelatory Situation Matching - Muhammad Nuzul Abraar; An-Nurrahmi; M. Haris Syahputra (LaKaspia, 2026)
The recitation of different Qur’anic verses for foreign delegations at Ayatollah Ali Khamenei’s state funeral prompted speculation that Iran was conveying hidden diplomatic messages through selective verse assignment. This study asks how verse selection for each delegation can be explained beyond ad hoc political signalling, and proposes Revelatory Situation Matching as an analytical mechanism for this purpose. Using a qualitative case study design, it examines twenty delegation–verse pairs drawn from approximately nine hours of official livestream footage. Historical revelatory situations were reconstructed from al-Wāḥidī’s Asbāb al-Nuzūl and the tafsīr literature; contemporary ceremonial situations were reconstructed from audiovisual observation and international media reports. Both corpora were coded independently through open, axial, and selective coding. The findings show that verse selection did not function as personalised political messaging to individual states, but as structural correspondence between historical revelatory situations and contemporary diplomatic circumstances: the strongest correspondences appeared among delegations associated with the Axis of Resistance, while partner states showed more moderate correspondences. The study concludes that Revelatory Situation Matching extends the function of asbāb al-nuzūl beyond hermeneutics into an analytical tool for contemporary Qur’anic reception, while Qur’anic Framing denotes the communicative effect produced once matched verses are performed before a public audience. These findings constitute an analytical reconstruction based on observable ceremonial patterns rather than a direct verification of the organisers’ decision-making process.